Heart and souls [videorecording (DVD)] - Underwood, Ron; Downey, Robert, Jr., 1965-; Grodin, Charles; Sedgwick, Kyra; Shue, Elisabeth; Sizemore, Tom, 1961-; Paymer, David; Woodard, Alfre, 1953- (MCA Universal Home Video, 1998)
Four souls learn why they are earthbound and tied to a hard driving executive--through him, they each have one chance to resolve the unfinished business in their lives.